The distributed development of quality courses for a virtual university - Martin Oliver; Claire Bradley; Tom Boyle (Association for Learning Technology, 2001)
The perceived need for global competition in higher education has led to the proliferation of projects and initiatives focused on the development of online education (see, for example, Smith and Oliver, 2000). Much resource and effort is being invested in this area, but there has been relatively little research into effective development and quality assurance models that can support the creation of online courses. Still less has been carried out that considers the particular developmental challenges posed by distributed teams of authors.